Behaviour dynamics of biochemistry reaction - Ribeiro, Mauricio A.; Szesz, Aryadyne Bueno Rocha; Novatski, Andressa; Lenzi, Giane Gonçalves; Lenz, Wagner Barth; Balthazar, Jose Manoel [UNESP]; Tusset, Angelo Marcelo (My University, 2020)
In this paper, we investigated the importance of the peroxidase in the enzymatic reactions of living organisms, analyzing the dynamic behavior of a mathematical model that describes the dynamics of the kinetic reaction of such an enzyme system. The methodology used for the dynamic analysis of the model was the maximum Lyapunov Exponent and the Bifucation Diagram, which allowed the determination of the chaotic and periodic regions of the system in addition to the analysis of Shannon's entropy in which the parameters that maximize and minimize the information entropy. We obtained as results the regions in which the parameters k1 and k3 are periodic or chaotic, confirming those found by the exponent of Lyapunov and the bifurcation diagram. Considering that the mathematical model has parametric sensitivity for certain values of the parameters of the peroxidase enzyme reaction constants.
Keywords: Dynamics system; Information entropy; Mathematical modeling